HUBUNGAN TINGKAT KEPATUHAN MINUM OBAT HIPERTENSI MENGGUNAKAN KUESIONER HILL-BONE TERHADAP KUALITAS HIDUP PASIEN DI PUSKESMAS PEKAUMAN BANJARMASIN SELATAN - Safitri, Sri Desi; Hartanto, Dedi; Mulyani, Tuty (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2024)
Hypertension is a disease that is the number one cause of death in the world every year. Based on measurements at ages ≥18 years, the highest hypertension prevalence data according to the province is South Kalimantan at 44.13%. One of the causes of the high prevalence of hypertension is due to low compliance in taking medication. Compliance is very necessary while undergoing hypertension treatment to reduce the impact and thus provide a good quality of life. The purpose of this study was to determine the relationship between the level of compliance using the Hill-Bone questionnaire on the quality of life of hypertensive patients at the Puskesmas Pekauman. This study used an observational method with a cross-sectional design to determine the picture of the level of compliance with the quality of life of hypertensive patients at the Puskesmas Pekauman. Data collection using the Hill-Bone questionnaire to determine adherence level and EQ-5D-5L questionnaire to determine patient's quality of life. The results of this study showed that of the 68 respondents, 3 people (4.40%) with a moderate level of compliance had a moderate quality of life, 59 people (86.80%) with a moderate level of compliance had a high quality of life and 6 people (8.8 %) with a high level of compliance have a high quality of life, which is obtained from Kendall's tau-B test, p-value = 0.000 < 0,05. It can be concluded that there is a significant relationship between compliance and quality of life in hypertension sufferers at the Puskesmas Pekauman.